Analisis Kemampuan Berpikir Kreatif pada Materi Cahaya Siswa Kelas Delapan SMP Xaverius Kota Lubuklinggau - Wahyu Arini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2017)
The purpose of this research is to describe students creative thinking ability in light matter, to know the students creative thinking ability in light matter when viewed from cognitive observation and affective observation, to know the difficulties experienced by students in achieving the indicators of creative thinking ability and determination solution to overcome student difficulties in achieving the indicators of creative thinking ability of class 8 SMP Xaverius Kota Lubuklinggau. The type of this research is descriptive qualitative, with case study research type. The subject of this research is all students of class 8 SMP Xaverius Kota Lubuklinggau. Data completion technique in this research is using technique triangulation that is cognitive observation technique, affective observation, and interview. Data analysis technique is descriptive qualitative analysis. The result showed that students thinking ability of class 8 junior Xaverius Kota Lubuklinggau still less creative 6,68 percent based on result of cognitive observation which was completed with interview result and creative enough category 57,74 percent result of affective observation. the recommendations that can be submitted in this research is the teacher will give equal opportunity to all students to be able to develop the ability of creative thinking in the learning process Keywords: Analysis, Creative Thinking, Light.